2021
DOI: 10.1093/nar/gkab117
|View full text |Cite
|
Sign up to set email alerts
|

RNA thermoswitches modulateStaphylococcus aureusadaptation to ambient temperatures

Abstract: Thermoregulation of virulence genes in bacterial pathogens is essential for environment-to-host transition. However, the mechanisms governing cold adaptation when outside the host remain poorly understood. Here, we found that the production of cold shock proteins CspB and CspC from Staphylococcus aureus is controlled by two paralogous RNA thermoswitches. Through in silico prediction, enzymatic probing and site-directed mutagenesis, we demonstrated that cspB and cspC 5′UTRs adopt alternative RNA structures that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 65 publications
(70 reference statements)
2
19
0
Order By: Relevance
“…In support of this, Kragh et al observed what they proposed to be a compensatory increase in cspD and cspB transcripts in cspA deletion mutants compared to their wild-type in response to desiccation [ 19 ]. This feature was also noticed in other bacterial species [ 41 , 55 , 68 ], indicative that Csps might regulate themselves and each other’s expression, possibly in a negative feedback loop manner as observed in other bacteria such as S. aureus for CspA or CspE regulating cspA expression in E. coli [ 30 , 44 , 112 , 117 ]. A triple csp deletion (∆ cspABE ) in Lactococcus lactis did not affect growth characteristics of the bacterium, an observation attributed to increased expression of the remaining csp genes [ 44 ].…”
Section: Csps Regulationsupporting
confidence: 63%
See 2 more Smart Citations
“…In support of this, Kragh et al observed what they proposed to be a compensatory increase in cspD and cspB transcripts in cspA deletion mutants compared to their wild-type in response to desiccation [ 19 ]. This feature was also noticed in other bacterial species [ 41 , 55 , 68 ], indicative that Csps might regulate themselves and each other’s expression, possibly in a negative feedback loop manner as observed in other bacteria such as S. aureus for CspA or CspE regulating cspA expression in E. coli [ 30 , 44 , 112 , 117 ]. A triple csp deletion (∆ cspABE ) in Lactococcus lactis did not affect growth characteristics of the bacterium, an observation attributed to increased expression of the remaining csp genes [ 44 ].…”
Section: Csps Regulationsupporting
confidence: 63%
“…These structural forms also increase the mRNA stability decreasing their degradation compared to the cspA mRNA structure at 37 °C [ 105 , 107 , 110 ]. This type of regulation is not unique to cspA only as translation of cspB, and cspC of S. aureus is also controlled by RNA thermoswitches [ 112 ]. In addition, Csp proteins are generally stable from degradation even under stress, presumably ensuring that they have an extended half-life to exert their influence [ 113 ].…”
Section: Csps Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…At 37°C, the energy provided by the increased temperature is sufficient to cause a structural switch that enables translation of the TF. Additional thermometers are found in many pathogens such as Salmonella Typhi and S. aureus ( Hussein et al, 2019 ; Brewer et al, 2021 ; Catalan-Moreno et al, 2021 ), and have been extensively reviewed ( Loh et al, 2018 ).…”
Section: Classification Of Base-pairing Acting Srnas According To Their Origins and Mechanisms Of Actionmentioning
confidence: 99%
“…This, on the one hand, supports the idea that these highly abundant proteins play a major role in the B. subtilis cell and, on the other hand, suggests that there is at least some functional overlap between them. In Staphylococcus aureus , the CspA protein is unique among the three cold shock proteins since it is the only one that is strongly constitutively expressed and important for the expression of the virulence factor staphyloxanthin [ 18 , 19 ]. It was shown that a single amino acid in CspA, a conserved proline residue, is responsible for this regulatory effect [ 18 ].…”
Section: Introductionmentioning
confidence: 99%